AGRARIAN REFORM UNDER THE REIGN OF JOKO WIDODO VIEWED FROM BASIC AGRARIAN LAW - Rizka Refliarny; Herawan Sauni; Hamdani Ma'akir (Universitas Bengkulu, 2020)
This study raises the issue of agrarian reform draft under the reign of President Joko Widodo. Agrarian reform became a priority program in the RPJMN of 2015-2019. Based on this matter, the writer analyzes the concept of agrarian reform during the reign of Joko Widodo terms of BAL. The nature of the study was a normative research with statute approach, which was done in four ways, namely descriptive, comparative, evaluative and argumentative. The results showed that the agrarian reform draft during the reign of Joko Widodo is a concept of land stewardship and land reform. The economic system leads to a form of capitalism. It is necessary to conduct refinement of content and material of BAL implementation in order to achieve the justice and the welfare of the nation and the State. The agrarian reform program should be carried out in stages in order to obtain the desired results. It requires the will, ability and active involvement of all elements of the state.